Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0165508
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Dyslexia Using Eye Tracking during Reading

Abstract: Dyslexia is a neurodevelopmental reading disability estimated to affect 5–10% of the population. While there is yet no full understanding of the cause of dyslexia, or agreement on its precise definition, it is certain that many individuals suffer persistent problems in learning to read for no apparent reason. Although it is generally agreed that early intervention is the best form of support for children with dyslexia, there is still a lack of efficient and objective means to help identify those at risk during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 47 publications
3
71
0
1
Order By: Relevance
“…An alternative paradigm to psycholinguisticsbased feature extraction is to instead represent raw recorded scanpaths over entire word sequences as 2D or 3D matrices and images (von der Malsburg et al, 2012;Martínez-Gómez et al, 2012;Benfatto et al, 2016;Mishra et al, 2017a). However, this paradigm has only been explored in a jointly labeled setting where gaze data is assumed to be available at test time.…”
Section: Background and Motivationmentioning
confidence: 99%
“…An alternative paradigm to psycholinguisticsbased feature extraction is to instead represent raw recorded scanpaths over entire word sequences as 2D or 3D matrices and images (von der Malsburg et al, 2012;Martínez-Gómez et al, 2012;Benfatto et al, 2016;Mishra et al, 2017a). However, this paradigm has only been explored in a jointly labeled setting where gaze data is assumed to be available at test time.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In 2015, the first method to screen dyslexia in Spanish was introduced; it used eye-tracking measures from 97 subjects (48 with dyslexia) [21]. Later in 2016, eye-tracking measures were also used to predict dyslexia for Swedish (185 subjects, 97 of then with high-risk of dyslexia) [2]. Both methods used Support Vector Machines.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…There were 9 participants at risk of having dyslexia or suspected of having dyslexia -Class M (Maybe)-(4 female, 5 male, M = 17.66, SD = 16.17). 2 The first language of all participants was English, although 84 participants spoke another language (mostly Spanish in the Texas area). A total of 224 participants reported having trouble with language classes at school.…”
Section: Participantsmentioning
confidence: 99%
“…Several experts have suggested that dyslexic individuals may have a mildly affected cerebellum, which could impair literacy as well as motor skill performance (Fawcett & Nicolson, 2004;Nicolson, Fawcett, & Dean, 2001;Stoodley & Stein, 2013). For example, dyslexic children spend a longer time to read when compared to nondyslexic children (Benfatto et al, 2016;de Luca, Marinelli, Spinelli, & Zoccolotti, 2017;Parka & Lombardino, 2013), walk significantly slower when asked to walk as fast as possible (Moe-Nilssen, Helbostad, Talcott, & Toennessen, 2003), and exhibit poorer performance when compared to normal reading children in a task involving isometric force production and control guided by visual feedback (de Freitas, Pedao, & Barela, 2014). For example, dyslexic children spend a longer time to read when compared to nondyslexic children (Benfatto et al, 2016;de Luca, Marinelli, Spinelli, & Zoccolotti, 2017;Parka & Lombardino, 2013), walk significantly slower when asked to walk as fast as possible (Moe-Nilssen, Helbostad, Talcott, & Toennessen, 2003), and exhibit poorer performance when compared to normal reading children in a task involving isometric force production and control guided by visual feedback (de Freitas, Pedao, & Barela, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The main idea is that the mild cerebellar insult would impair the ability of dyslexic individual to learn how to perform tasks with automaticity, with much less conscious efforts while reading, writing, and performing other tasks such as postural control (i.e., cerebellar hypothesis) (Fawcett & Nicolson, 2004). For example, dyslexic children spend a longer time to read when compared to nondyslexic children (Benfatto et al, 2016;de Luca, Marinelli, Spinelli, & Zoccolotti, 2017;Parka & Lombardino, 2013), walk significantly slower when asked to walk as fast as possible (Moe-Nilssen, Helbostad, Talcott, & Toennessen, 2003), and exhibit poorer performance when compared to normal reading children in a task involving isometric force production and control guided by visual feedback (de Freitas, Pedao, & Barela, 2014). Furthermore, dyslexic children manifest poor performance during a task requiring postural control (Brookes, Tinkler, Nicolson, & Fawcett, 2010;Moe-Nilssen et al, 2003;Patel, Magnusson, Lush, Gomez, & Fransson, 2010;Pozzo et al, 2006;Stoodley, Fawcett, Nicolson, & Stein, 2005;Vieira, Quercia, Michel, Pozzo, & Bonnetblanc, 2009).…”
mentioning
confidence: 99%